PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAUDARI KEMANDIRIAN BELAJAR SISWA PADA MATERI HIMPUNAN DI KELAS VII SMP NEGERI 01 TAYAN HULU - Anna Kristina Keriahenta Barus; Marhadi Saputro; Iwit Prihatin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the application of the Problem Based Learning learning model to mathematical communication skills in terms of independent learning on set material in class VII SMP Negeri 01 Tayan Hulu. The research form used is quasi-experimental designs, with a 2×3 factorial design. The population in this study were students of class VII A and students of class VII B. The sample in this study was one class selected by cluster random sampling. Data collection techniques used are direct communication techniques and measurement techniques with data collection tools in the form of questionnaires and test questions in the form of essays. The data analysis technique used was the analysis of two dissimilar cell paths with the normality test using the Lilifors test, homogeneity using the Bartlett test and continued with the multiple comparison test using the Scheffe method. The results of this study are (1) the mathematical communication of students who follow the problem-based learning model is better than students who follow the conventional learning model, (2) the ability of mathematical communication between students who have high learning independence is better than moderate after the implementation of the model learning problem based learning. (3) students' mathematical communication skills in the moderate learning independence category were better than students in the low learning independence category after applying the problem-based learning model. (4) at the level of independent learning, problem-based learning models provide better mathematical communication skills than conventional learning models.